Analysis of the quality of knowledge on employees of PT. Hadji Kalla Toyota - Muhammad Jihad Firman; Beddu Lahi; Fathul Khair (Pinisi Business Administration Review, 2022)
Knowledge is more aimed at efforts to develop and maintain the company's competitiveness. In building and maintaining competitiveness, intellectual basis must exist in various fields within the company. With the increasing specialization in the company, the role of knowledge management is increasingly needed in various aspects of the company. The purpose of this study was to determine the analysis of the quality of knowledge on employees of PT. Hadji Kalla Toyota. The type of data in this study consists of qualitative data. The research results are PT. Hadji Kalla Toyota is ready to apply knowledge in his company. Conceptually, a knowledge management audit is conducted to obtain an overview of the knowledge possessed and needed by the organization, the readiness of the organization to facilitate learning, and the quality of knowledge management processes.